2007
DOI: 10.1021/ja073189o
|View full text |Cite
|
Sign up to set email alerts
|

The Photoarrangement of α-Santonin is a Single-Crystal-to-Single-Crystal Reaction:  A Long Kept Secret in Solid-State Organic Chemistry Revealed

Abstract: α-Santonin 1 is a naturally occurring sesquiterpene lactone of significant historical interest. Not only is its solid-state photochemistry the oldest documented for an organic compound, but it is also the first drug to have been formulated in the United States. Not surprisingly, while its photochemical behavior in solution has been relatively well-established, its solid-state photoreactivity has not been thoroughly characterized. In this communication, with a combination of polarizing microscopy, single-crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 11 publications
2
74
0
1
Order By: Relevance
“…This observation of crystal motility was to become the first documented report of the thermosalient (TS) effect (Hüpf-Effekt)-the propensity of certain crystals to hop and leap when heated over a phase transition 9,10,18,19 . Two polymorphs, yellow form (a) and red form (b), were characterized 17 .…”
mentioning
confidence: 89%
“…This observation of crystal motility was to become the first documented report of the thermosalient (TS) effect (Hüpf-Effekt)-the propensity of certain crystals to hop and leap when heated over a phase transition 9,10,18,19 . Two polymorphs, yellow form (a) and red form (b), were characterized 17 .…”
mentioning
confidence: 89%
“…[5,6] Photochromic materials have received considerable attention for their potential applications in information display devices, high-density memory, and other high-tech areas. While purely organic [7] or inorganic [8] photochromic materials have been known for a long time, much attention has recently been dedicated to the development of photochromic inorganic-organic hybrids because of the novel and intriguing properties arising from the interactions between both organic and inorganic components. Structurally well-defined hybrids will give us better insight into these interactions.…”
mentioning
confidence: 99%
“…Overall, it is a stepwise reaction. After irradiation by UV light with a wavelength of more than 300 nm, [21] R is promoted to the first singlet excited state 1 (np*). Subsequently, the excited-state conversions take place on the surface crossings (pp*) state decays nonradiatively through ISC to the ground state, the reaction preferentially yields A-P-II through A-TS-II, both favored thermodynamically and dynamically.…”
Section: The Proposed Favorable Photoinduced Rearrangement Reaction Pmentioning
confidence: 99%
“…In 1968, Matsuura and co-worker assumed that during the reaction an unstable intermediate is formed which subsequently yields a product through Diels-Alder and [2+2] cycloaddition reactions. [20] The critical intermediate, cyclopentadienone, involved in the subsequent reactions in the crystal, was recently characterized by Garcia-Garibay et al [21] It has been reported that under ultra-violet light irradiation, a-santonin, designated by R, undergoes a ring-closure reaction leading to a vital intermediate characterized by a three-membered carbon ring, denoted as INT. A subsequent carbon-bond cleavage takes place on the newly formed ring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation